2020
DOI: 10.1002/nop2.606
|View full text |Cite
|
Sign up to set email alerts
|

Well‐being of nurses and working conditions—Are polish nurses different from doctors and midwives in terms of professional quality of life?

Abstract: Aim The aim of the study is to assess the differences in the professional quality of life between nurses, midwives and doctors. Design Cross‐sectional study. Methods A total of 297 participants were surveyed: 165 nurses, 101 doctors and 31 midwives. We used ProQol questionnaire with three subscales (compassion satisfaction ‐CS, burnout‐ B, compassion fatigue‐CF and own questionnaire (social‐demographics data). Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 21 publications
1
3
0
2
Order By: Relevance
“…In fact, being a physician was associated with better health status (r = 0.237; p -value = 0.002) and individual health perception (r = 0.283; p -value = < 0.001). A better wellbeing perception was positively associated with lower work seniority in both groups, similar to other research results [ 35 , 45 ]. One possible explanation might be found in a peculiarity of the healthcare profession, which is the presence of different stressors that could lead to the development of occupational burnout, hence reducing the overall quality of life.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In fact, being a physician was associated with better health status (r = 0.237; p -value = 0.002) and individual health perception (r = 0.283; p -value = < 0.001). A better wellbeing perception was positively associated with lower work seniority in both groups, similar to other research results [ 35 , 45 ]. One possible explanation might be found in a peculiarity of the healthcare profession, which is the presence of different stressors that could lead to the development of occupational burnout, hence reducing the overall quality of life.…”
Section: Discussionsupporting
confidence: 91%
“…The majority of the existing literature has focused on evaluating the perception of COVID-19 pandemic management among HCWs and the general population [ 30 , 31 , 32 , 33 , 34 ], whereas few investigations [ 35 , 36 , 37 ] have currently assessed the difference between physicians and nurses in the perception of wellbeing and stress-coping strategies, particularly focusing on whether the nursing profession might represent a risk factor itself or whether additional factors may also affect this vulnerability.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Estudios informan que la CVT de las enfermeras no es de las mejores, encontrándose que sus niveles oscilan entre medios a bajos, influyendo en tal condición factores sociodemográficos y laborales entre ellos, la edad, nivel educativo, número de hijos, dependientes a cargo, experiencia laboral, (16) trabajo por turnos, insuficiente cantidad de personal, niveles altos de carga psicológica generados por presión de tiempo, responsabilidad por la salud y vida del paciente, presencia de violencia física y emocional. (17) En ese sentido, esta revisión se propuso como objetivo identificar la literatura existente sobre los niveles de satisfacción e insatisfacción con la calidad de vida en el trabajo de las enfermeras en América Latina.…”
Section: Introductionunclassified
“…The research conducted in 2000 and 2014 in the European Union countries showed that Poland ranks sixth from last in terms of the number of nurses per 1000 inhabitants [ 25 ]. It is necessary to emphasise that two-thirds of the population of Polish nurses fall into the 41–60 age range, and almost 85% of them are over 40 [ 26 ]. The study results indicate statistically significant relationships between occupational burnout and occupational stress among nurses, as well as differentiation in terms of education, age and seniority [ 27 ].…”
Section: Introductionmentioning
confidence: 99%